NFL 100 : a century of pro football - Fleder, Rob; MacCambridge, Michael, 1963-; Manning, Peyton (Abrams, 2019)
"Timed to coincide with the National Football Leagues 100th anniversary, NFL 100 celebrates the history of Americas most popular and highly watched sport. From its humble beginnings in Canton, Ohio, to its emergence as a sport cherished by millions, all the key moments and famous athletes are honored within the pages of this handsomely produced book. In addition to the lively text, and action and portrait photography, the story of the game and the context in which it grew are animated by original lists, charts, creative statistics, and infographics, along with beautiful photos of the evolving equipment and artifacts essential to the story of the sport. A perfect gift, NFL 100 will be cherished by every football fan, new or old."--Amazon.